Treatment Role Of Recombinant Human Growth Hormone Combined With Calcium Lysine Phosphate Hydrogen Granule In Children Suffering From Idiopathic Short Stature (Journal of Pharmaceutical Negative Results, 2023)
Objective: to learn more about the therapeutic impact of treating children with idiopathic short stature with calcium lysine phosphate hydrogen calcium granules and recombinant human growth hormone. Methods: From May 2021 to May 2022, 114 children with idiopathic low stature received treatment at Marjan Teaching Hospital. They were split into a control group and a treatment group, each of which had 57 instances, depending on the pharmaceutical differences. The treatment group received oral lysine phosphate hydrogen calcium granules, 5 g/time, twice daily, while the children in the control group received subcutaneous injections of recombinant human growth hormone solution, 0.033-0.050 mg/kg, once daily. The two study groups have been received care for a full year. Results: Following treatment, the overall success ratio in the treatment group was meaningfully greater than that in the control group (95.21% vs 82.31%), (P value lower than 0.05). The two groups experienced much faster development rates in terms of height and weight, bone age, and growth. The serological parameters and bone metabolism indices in both groups significantly increased following therapy (P value lower than 0.05). Conclusion: In the treatment of children with idiopathic short stature, calcium lysine phosphate hydrogen granules and recombinant human growth hormone are successful in promoting the growth of height in these children. To encourage the improvement of bone metabolism indicators, it has some clinical application benefit.